SIMULASI JARINGAN METRO ETHERNET DENGAN APLIKASI CIS-CO PACKET TRACER VERSI 6.2.0 - Naufal Taufiqul Hakim; Hijroh Tamamil Gina; Apriliano Chandra Diva; Gilang Gemilang; Didik Aribowo (Jurnal Sains dan Teknologi, 2023)
Metro ethernet is an ethernet-based high-capacity data network solution service that provides flexibility, simplicity and quality of service (qos) to business customers of internet service providers (isp) and other licensed service providers (olo). Ethernet has speeds of up to 10 gbps and with distances of tens or even hundreds of kilometers. The method used in writing this journal is to use the literature review method, namely the method used is the result of an analysis of various previously published scientific article information. Utilization of metro ethernet in its benefits, namely managing risk intelligently, in its management functioning and running independently, namely utilization for each operational, functional and administrative. Reliability, in operation metro ethernet will detect and track discovery to report that it is in a connection failure situation in its performance measurement. Flexibility, support for various services and transportation. Cost-efficiency, simple and highly maintainable metro ethernet network scalability, supports speeds up to 10 gbps. This research was made to find out more about the uses of the metro ethernet network and the configuration on metro ethernet.